1888 Ky. Acts 139 - (:unkn) unknown (My University, 1888)
Unlawful for Other Than Regular Militia to Drill, Ch. 1525,§ 1: It shall be unlawful for any body of men whatever, other than the regular organized militia of this Commonwealth, and the troops of the United States, to associate themselves together as a military company or other armed organization
Keywords: MILITIAS